Magnetic resonance imaging knee joint measurements for the prediction of the population at risk of anterior cruciate ligament tear injuries - Raiyan, Mohammed; Fahim, Shaikh M.; Nigesh, Madhusudhan D. (International Journal of Research in Orthopaedics, 2025)
Background: This study aims to investigate whether patient-related anterior cruciate ligament (ACL) damage is associated with measures of various knee joint components. Methods: Patients who had magnetic resonance imaging (MRI) and suffered from ACL injuries were included in this retrospective case-control study. There was also a control group of individuals who had normal MRI results for knee diseases. The following 14 knee variables were gathered: lateral and medial (MFC) femoral condyle sphere diameter; lateral and medial tibial plateau length; patella tendon horizontal and vertical diameter; lateral meniscus (LM) posterior horn height, length, depth, and volume; and medial meniscus (MM) posterior horn height, length, depth, and volume. The two groups were compared using a multivariate logistic regression that took into account the patella tendon horizontal diameter, MFC sphere diameter, MM posterior horn length, MM volume, LM posterior horn depth, and receiver operating characteristic curve. Results: We enrolled 98 patients in total; 48 had ACL injuries, and 50 had normal knee MRIs as a comparison group. The results of the logistic regression analysis showed that the following factors independently predicted the risk of ACL rupture: decreased MM posterior horn length (OR=0.45; 95% CI=0.33-0.630; p<0.001), increased LM posterior horn depth (OR=1.78; 95% CI=1.37- 2.03; p<0.001), and MFC sphere diameter (OR=1.27; 95% CI=1.01-1.60; p=0.0354). Conclusions: Individuals with an ACL injury had shorter MM posterior horns, deeper LM posterior horns, larger MFC sphere diameters.